2011
DOI: 10.1186/1475-2875-10-147
|View full text |Cite
|
Sign up to set email alerts
|

Community perceptions of malaria and vaccines in the South Coast and Busia regions of Kenya

Abstract: BackgroundMalaria is a leading cause of morbidity and mortality in children younger than 5 years in Kenya. Within the context of planning for a vaccine to be used alongside existing malaria control methods, this study explores sociocultural and health communications issues among individuals who are responsible for or influence decisions on childhood vaccination at the community level.MethodsThis qualitative study was conducted in two malaria-endemic regions of Kenya--South Coast and Busia. Participant selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 14 publications
7
60
0
2
Order By: Relevance
“…Upon investigating the acceptability and attitudes of child caregivers toward a malaria vaccine in all eight regions of Kenya, it was found that the majority of caregivers would support the introduction of a malaria vaccine. Previous studies in Kenya, Tanzania, Mozambique, and Ghana similarly demonstrated a widespread support for a possible new malaria vaccine [11-13]. Reduced mortality and morbidity were the main reasons stated for acceptance of the vaccine, whereas many would not accept the vaccine due to a combination of possible side effects and incomplete vaccine protection.…”
Section: Discussionmentioning
confidence: 99%
“…Upon investigating the acceptability and attitudes of child caregivers toward a malaria vaccine in all eight regions of Kenya, it was found that the majority of caregivers would support the introduction of a malaria vaccine. Previous studies in Kenya, Tanzania, Mozambique, and Ghana similarly demonstrated a widespread support for a possible new malaria vaccine [11-13]. Reduced mortality and morbidity were the main reasons stated for acceptance of the vaccine, whereas many would not accept the vaccine due to a combination of possible side effects and incomplete vaccine protection.…”
Section: Discussionmentioning
confidence: 99%
“…These groups receive 3 doses of RTS,S/AS01 vaccine at 1 mo intervals. 9,[19][20][21] Initial results show that the RTS,S/AS01 vaccine reduced malaria by 50% in children 5-17 mo of age during the 12 mo after vaccination. These results are promising and consistent with findings from phase 2 trials.…”
Section: Csp Protein/ Rts Vaccinementioning
confidence: 99%
“…However, the burden of malaria is very well known to the community members and there is a critical community demand for a malaria vaccine. 67,68 This demand for a vaccine is likely to make community acceptance of a new vaccine easier. On the other hand, the high demand for a malaria vaccine may make community members perceive a partially efficacious malaria vaccine as a magic bullet for malaria control that could lead to a reduction in the use of other malaria control interventions such as bednets.…”
Section: Community Acceptance Of Rtss Malaria Vaccinementioning
confidence: 99%